P‐197: Enhanced Out‐coupling Efficiency of Organic Light‐Emitting Diodes using Nano‐sized Pixel Defining Layer. Issue 1 (2nd June 2017) - Hwang, Ha; Shim, Yong Sub; Lee, Dong Jun; Kim, Jae Geun; Lee, Ju Sung; Choi, Junhee; Park, Young Wook; Ju, Byeong-Kwon
Abstract : In this study, organic light‐emitting diodes with enhanced out‐coupling efficiency were demonstrated by inserting nano‐sized pixel defining layer (nPDL). Photoresist is used for composing the nPDL through a laser inteference lithogrphy (LIL) process. The nPDL increases optical efficiency by the Bragg's diffraction from periodic structures of photonic crystal and the corrugated metallic mirror.